TRIALLING PISA PROBLEMS IN SECONDARY SCHOOL - Denny . Haris (Universitas Negeri Medan, 2016)
AbstrakThis article is a report of trialing PISA problems designed in secondary school. This report explores students’ strategies in solving PISA problems which has three criterion, namely content, context and competencies. Hopefully, first, they should be usual with the PISA problems related to description of the situation and the students have to discover and solve the problems with their own strategies. Second, they can solve the problem without require applying formulas or procedures, so that they have sense to mathematics.Keyword: PISA Problem